Reinstatement of the genus Heteroglenea Gahan, with four new combinations, four new synonyms and three new species (Coleoptera: Cerambycidae: Lamiinae: Saperdini) - Lin, Meiying; Montreuil, Olivier; Tavakilian, Gérard; Yang, Xingke (Zootaxa, 2009)
Heteroglenea Gahan, 1897 is reinstated from the synonyms of Glenea (sensu stricto) Newman, 1842, and is redefined. Four taxa are transferred to Heteroglenea: H. fissilis (Breuning, 1953) comb. nov., H. bastiensis (Breuning, 1956) comb. nov., H. momeitensis (Breuning, 1956) comb. nov. and H. mediodiscoprolongata (Breuning, 1964) comb. nov. Glenea mimoluctuosa Breuning, 1968 is considered a junior synonym of H. mediodiscoprolongata (Breuning, 1964). Glenea (G.) palawana Breuning, 1956, G. (G.) guadalcanalana Breuning, 1958, and G. (G.) hamabovola Hayashi, 1975, are considered junior synonyms of H. glechoma (Pascoe, 1867). Heteroglenea vicinalis Lin et Yang sp. nov. from Nepal and India, H. gemella Lin et Yang sp. nov. from Nepal and H. dolosa Lin et Yang sp. nov. from Laos are described. Heteroglenea fissilis and H. mediodiscoprolongata are newly recorded from China. Photographs of habitus and terminalia and a key to the nine valid species of Heteroglenea are presented.